Chemically chargeable photo battery - Thimmappa, Ravikumar; Paswan, Bhuneshwar; Gaikwad, Pramod; Devendrachari, Mruthyunjayachari Chattanahalli; Kotresh, Harish Makri Nimbegondi; Mohan, Ramsundar Rani; Alias, Joy Pattayil; Thotiyl, Musthafa Ottakam (Journal of Physical Chemistry C, 2015)
Here we show a surrogate strategy for power production, wherein light is used to actuate a discharge Chemistry in the cathode of an aqueous rechargeable battery (ARB). The proposed photo battery consists of a titaninm nitride photoanode, promising. cathode:material iron(III) hexacyanoferrate(II) as the battery active species, and Na2S2O8 as the chemical charging agent The photo battery delivered negligible capacity in the dark and the capacity shot up to 77.8 mAh/g when artificially shined light, confirming that the battery chemistry is light driven. In the ambient light, the device retained 72% of its artificial light discharge capacity with a stable cycling for more than 100 cycles. Further, an unprecedented means for charging the battery rapidly is presented using Na2S2O8 and it revitalized the battery in 30 s without any external bias. This methodology of expending a photoanode extends to a battery that is free from dissolution of active materials, irreversible structural changes, spontaneous deinsertion reactions, and safety concerns commonly encountered in the state of the art anode materials in ARBs. Apart from bringing out a sustainable way for power production, this device opens up avenues for charging the battery in the likely events of electrical input unavailability, while solving the critcial issues of longer charging time and higher charging voltage.

Geometrical isomerism directed electrochemical sensing - Kottaichamy, Alagar Raja; Begum, Shabbah; Devendrachari, Mruthyunjayachar Chattanahalli; Bhat, Zahid Manzoor; Thimmappa, Ravikumar; Kotresh, Harish Makri Nimbegondi; Vinod, Chathakudath Prabhakaran; Thotiyl, Musthafa Ottakam (Analytical Chemistry, 2020)
We report the independent role of isomerism of secondary sphere substituents over their nature, a factor often overlooked in molecular electrocatalysis pertaining to electrochemical sensing, by establishing that isomerism redefines the electronic structure at the catalytic reaction center via geometrical factors. UV-vis spectroscopy and X-ray photoelectron spectroscopy suggest that a substituent's isomerism in molecular catalysts conjoins molecular planarity and catalytic activation through competing field effects and resonance effects. As a classical example, we demonstrate the influence of isomerism of the -NO2 substituents for the electrocatalytic multi electron oxidation of As(III), a potentially important electrochemical pathway for water remediation and arsenic detection. The isomerism dependent oxidative activation of catalytic center leads to a nonprecious molecular catalyst capable for direct As(III) oxidation with an experimental detection limit close to WHO guidelines. This work opens up an unusual approach in analytical chemistry for developing various sensing platforms for challenging chemical and electrochemical reactions.

Unprecedented isomerism-activity relation in molecular electrocatalysis - Kottaichamy, Alagar Raja; Begum, Shabbah; Nazrulla, Mohammed Azeezulla; Dargily, Neethu Christudas; Devendrachari, Mruthyunjayachari Chattanahalli; Bhat, Zahid Manzoor; Thimmappa, Ravikumar; Kotresh, Harish Makri Nimbegondi; Vinod, Chathakudath Prabhakaran; Thotiyl, Musthafa Ottakam (Journal of Physical Chemistry Letters, 2020)
The role of electrocatalysts in energy storage/conversion, biomedical and environmental sectors, green chemistry, and much more has generated enormous interest in comprehending their structure-activity relations. While targeting the surface-to-volume ratio, exposing reactive crystal planes and interfacial modifications are time-tested considerations for activating metallic catalysts; it is primarily by substitution in molecular electrocatalysts. This account draws the distinction between a substituent's chemical identity and isomerism, when regioisomerism of the -NO2 substituent is conferred at the ``alpha'' and ``beta'' positions on the macrocycle of cobalt phthalocyanines. Spectroscopic analysis and theoretical calculations establish that the beta isomer accumulates catalytically active intermediates via a cumulative influence of inductive and resonance effects. However, the field effect in the alpha isomer restricts this activation due to a vanishing resonance effect. The demonstration of the distinct role of isomerism in substituted molecular electrocatalysts for reactions ranging from energy conversion to biosensing highlights that isomerism of the substituents makes an independent contribution to electrocatalysis over its chemical identity.

Fuel from waste: electrosynthesizing ammonia directly from agricultural digestate through ligand isomerization - Mendhe, Rahul Mahadeo; Mondal, Ritwik; Kottaichamy, Alagar Raja; Haridas, Akshay; Kotresh, Harish Makri Nimbegondi; Vinod, Chathakudath Prabhakaran; Thimmappa, Ravikumar; Thotiyl, Musthafa Ottakam (Green Chemistry, 2024)
We demonstrate that the catalytic metal centre for ammonia production can be selectively activated with only a slight alteration in ligand isomerization (alpha and beta isomers), making it practical and effective even for agricultural effluents. With almost 90% faradaic efficiency, the beta isomer generates approximately 0.64 mg h-1 cm-2 of ammonia. Energy-efficient ammonia recovery is made possible by the interfacial proton charge assembly that beta-isomerization creates, which attracts the reacting nitrate and repels the competing hydronium ions. With minimal energy consumption, this isomerization approach can interconvert agricultural effluents into ammonia fuel, reaching up to 84% of its theoretical yield and maintaining stability over 100 hours of continuous electrolysis. Ligand isomerization driven ammonia electrosynthesis from agricultural waste water.

Ligand isomerization driven electrocatalytic switching - Kottaichamy, Alagar Raja; Nazrulla, Mohammed Azeezulla; Parmar, Muskan; Thimmappa, Ravikumar; Devendrachari, Mruthyunjayachari Chattanahalli; Vinod, Chathakudath Prabhakaran; Volokh, Michael; Kotresh, Harish Makri Nimbegondi; Shalom, Menny; Thotiyl, Musthafa Ottakam (ANGEWANDTE CHEMIE-INTERNATIONAL EDITION, 2024)
Keywords: Catalysts; CO2 reduction; O-2 REDUCTION; oxygen reduction